A techno-economic analysis of ethanol production from hydrolysis of cellulose with nanoscale magnetic solid acid catalysts - Ault, Trevor Joseph (Kansas State University, 2012)
Acid catalysts have been shown to be very successful in the pretreatment of cellulosic biomass to improve glucose yield and improve overall yield of ethanol. This report presents the results of a techno-economic study that looks into the use of nanoscale magnetic solid acid catalysts for glucose production. Magnetic solid acid catalysts are an improvement over using diluted acid due to eliminating acid-waste generation and corrosion hazards. Their magnetic nature also allows them to be easily separated from reaction products by an external magnetic force. After the technology is analyzed, a series of unit operations is proposed to go from the laboratory scale to the industrial plant scale. The next step was to develop material and energy balances using HYSYS process simulation software. Capital and operating costs are estimated and all the information is combined into a discounted cash flow economic model. The economic portion of the report uses a probabilistic cost assessment. It is used to quantify the range of risks in the project from swings in feedstock costs, differences in yield from catalysts, and any other significant variables. Both capital costs (initial equipment & construction investment) and operating costs (feedstock supply, chemicals, and personnell) are included with ranges of error based on databases and expert opinion. This method of evaluating investment efficiency can be helpful for predicting the cost benefits of proposed future research. The yield and percent catalyst magnetically recovered is assumed based on laboratory research to simplify the model. A 2000 metric tons of biomass per day facility was analyzed. Using the magnetic solid acid catalyst technology, the capital costs are estimated to be $160 million and this technology saves around 10% of capital costs compared to ethanol plants that uses conventional acid hydrolysis. The yield of the magnetic solid acid catalysts should be around 75% to compete with existing ethanol technologies. The metric used for this report is the discount profitability index (DPI) which is the ratio of future cash flows divided by investment. A DPI “hurdle rate” of 1.3 is used, which is similar to industry economic metrics of projects that include new process plants. The calculated DPI for the project is 1.38 DPI which is higher than using conventional cellulose treatment technologies. The recommendation is continue to study this technology’s large scale applicability before attempting any plant pilot studies.
Keywords: Solid acids; Magnetic nanoparticles; Biomass; Hydrolysis; Heterogeneous catalysis; Economic evaluation; Chemical Engineering (0542); Energy (0791); Engineering, Agricultural (0539)